Evolution of rat hepatitis E virus: recombination, divergence and codon usage bias - Liang Zhao; Yangmei Huang (Acta Virologica, 2023)
Rat hepatitis E virus (RHEV/HEV-C1, species Rocahepevirus ratti) is an emerging zoonotic pathogen, posing an increasing threat to public health worldwide. This study was conducted for better understanding the epidemiology and evolution of RHEV. The isolates sampled so far can be divided into two major genotypes designated a and b. According to the phylogeography, while type a has been detected in four continents, type b is restricted to East and Southeast Asia. Recombination analysis identified three chimeric isolates. Bayesian coalescent analysis suggested that RHEV began to expand around 1956 and was evolving at a high rate. Codon usage bias analysis revealed that RHEV genes are rich in G/C and have additional bias independent of compositional constraints. In codon usage, RHEV is both similar to and different from the major host Norway rat (Rattus norvegicus). Furthermore, unlike many other mammalian RNA viruses, RHEV does not mirror hosts’ marked suppression of “CG” and “TA”.